(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Multidrug resistance (MDR) exhibited by some strains of Escherichia coli may be due to acquiring mobile genetic element (R-plasmid) by the bacteria, or intrinsically induced by inappropriate use of antibiotics by the hosts. Infection by such strains may result to prolonged illness and greater risk of death. The study evaluated the impact of curing on antibiotic resistance on selected clinical isolates of E. coli. Twenty clinical isolates of E. coli from our previous studies were re-characterized using conventional microbiological techniques. Antibiotic sensitivity testing was determined by disk diffusion method, MDR selected based on resistance to â‰¥ 2 classes of antibiotics. Multiple antibiotic resistance (MAR) index was determined as ratio of the number of antibiotic resisted to the total number of antibiotics tested and considered significant if â‰¥. 0.2. The isolates that showed significant MAR index were subjected to plasmid curing using acridine orange, thereafter, profiled for plasmid and the cured ones were re-tested against the antibiotics they initially resisted. Out of the 20 isolates, 19 (95%) were confirmed as E. coli, all (100%) of which were MDRs, which was highest against augmentin (78.9%) followed by amoxacillin (52.6%). However, after the plasmid curing only 6 (31.6%) out of the 19 isolates cured retained significant MAR index and the level of the significance had reduced drastically in 16 (84.2%) isolates. Conclusively, curing assay can completely eliminate R-plasmid acquired resistance. More studied on plasmid curing agents for possible augmentation of the agents into antibiotics may see the rise of successful antibiotic era again.